2019
DOI: 10.1021/acs.nanolett.8b04160
|View full text |Cite
|
Sign up to set email alerts
|

Voltage Control of a van der Waals Spin-Filter Magnetic Tunnel Junction

Abstract: Atomically thin chromium triiodide (CrI 3 ) has recently been identified as a layered antiferromagnetic insulator, in which adjacent ferromagnetic monolayers are antiferromagnetically coupled 1,2 . This unusual magnetic structure naturally comprises a series of anti-aligned spin filters which can be utilized to make spin-filter magnetic tunnel junctions with very large tunneling magnetoresistance (TMR) 3-6 . Here we report voltage control of TMR formed by four-layer CrI 3 sandwiched by monolayer graphene conta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
142
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(150 citation statements)
references
References 32 publications
5
142
2
1
Order By: Relevance
“…However, when the magnetic field is enough to drive the bilayer into fully spin‐polarized states, the suppression in the tunneling is lifted. For the case of four‐layer CrI 3 , a large tunneling magnetoresistance ratio exceeding 25 000% has been reported at zero gate voltage (Figure C) . An obvious shift of the thresholds in these curves toward a positive gate bias may be caused by changes of Fermi level or magnetic proximity effects induced by CrI 3 in graphene contacts …”
Section: Progress On Van Der Waals Magnets and Heterostructuresmentioning
confidence: 83%
See 3 more Smart Citations
“…However, when the magnetic field is enough to drive the bilayer into fully spin‐polarized states, the suppression in the tunneling is lifted. For the case of four‐layer CrI 3 , a large tunneling magnetoresistance ratio exceeding 25 000% has been reported at zero gate voltage (Figure C) . An obvious shift of the thresholds in these curves toward a positive gate bias may be caused by changes of Fermi level or magnetic proximity effects induced by CrI 3 in graphene contacts …”
Section: Progress On Van Der Waals Magnets and Heterostructuresmentioning
confidence: 83%
“…39 C, Tunneling magnetoresistance ratio at different gate voltages for four layers CrI 3 MTJ. 108 Figure 6D). This in turn gives rise to an observed 160% magnetoresistance, corresponding to a spin polarization of 66% at the Fermi level.…”
Section: Magnetic Tunnel Junctionsmentioning
confidence: 96%
See 2 more Smart Citations
“…According to the Mermin–Wagner theorem,18 2D long‐range FM order cannot exist in an isotropic magnetic system. Recently, people found that 2D layered CrI 3 ,19–27 Cr 2 Ge 2 Te 6 ,28 and CrSiTe 3 29 possesses intrinsic magnetocrystalline anisotropy against thermal fluctuations. However, the Curie temperatures of CrI 3 , Cr 2 Ge 2 Te 6 , and CrSiTe 3 are only dozens of Kelvins.…”
Section: Introductionmentioning
confidence: 99%